Does bank health matter after converted to sharia? Case study of Bank Aceh - Iswadi Bensaadi; Zulkifli Yusuf; Darmawati Muchtar; Mukmim Alamsyah Putra Matondang (Universitas Negeri Padang, 2021)
AbstractThe health of a bank is a reflection of bank ability to continue to operate with good performance. This study examined the differences in bank health and the trend of bank health before and after being converted into Islamic banks. This study used quarterly financial statements data from 2012 to 2020, with 18 observations before converting and 18 observations after converting into islamic banks. The results showed that bank health was lower when operating under the Islamic system compared to under a conventional system. Others showed that there was no difference in the trend of bank health based on the Islamic system and the non-Islamic system. The lower of bank health after being converted to Islamic banks showed that the efficiency of banks was lower after being converted than before being converted to Islamic. Islamic bank management needs to increase attention to improve bank efficiency by optimally utilizing assets. TRANSLATE with x EnglishArabicHebrewPolishBulgarianHindiPortugueseCatalanHmong DawRomanianChinese SimplifiedHungarianRussianChinese TraditionalIndonesianSlovakCzechItalianSlovenianDanishJapaneseSpanishDutchKlingonSwedishEnglishKoreanThaiEstonianLatvianTurkishFinnishLithuanianUkrainianFrenchMalayUrduGermanMalteseVietnameseGreekNorwegianWelshHaitian CreolePersian // TRANSLATE with COPY THE URL BELOW Back EMBED THE SNIPPET BELOW IN YOUR SITE Enable collaborative features and customize widget: Bing Webmaster PortalBack//